A multicenter round robin test of PD-L1 expression assessment in urothelial bladder cancer by immunohistochemistry and RT-qPCR with emphasis on prognosis prediction after radical cystectomy - Eckstein, Markus; Nitschke, Katja; Erben, Philipp (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.24531 Markus Eckstein, Ralph M. Wirtz, Carolin Pfannstil, Sven Wach, Robert Stoehr, Johannes Breyer, Franziska Erlmeier, Cagatay Günes, Katja Nitschke, Wilko...
Gesehen am 19.07.2019